Techno-security in an age of globalization : perspectives from the Pacific Rim - Simon, Dennis Fred (New York : M.E. Sharpe, 1997)
An East Gate book.
Keywords: Competition, International; Pacific Area -- Economic policy; Technological innovation -- Economic aspects -- Pacific Area